2015
DOI: 10.1007/s10971-015-3808-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, photocatalytic, and antimicrobial activities of cobalt-doped tin oxide nanoparticles

Abstract: In this study, pure and Co-doped tin oxide (SnO 2 ) nanoparticles were synthesized by sol-gel method, and the effect of Co-doping on the structural, optical, photocatalytic, and antimicrobial activities was studied. The prepared samples were characterized by X-ray diffraction (XRD), highresolution transmission electron microscopy, energy-dispersive X-ray spectroscopy, UV-visible diffuse reflectance spectroscopy, and N 2 adsorption/desorption analysis. The XRD patterns of all the samples are identified as tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…All the Zr-doped SnO 2 NPs illustrate improved bacteriological retardant performance equated to the pristine sample besides the experienced pathogenic microbes. The inadequate antibacterial movement detected for the pristine SnO 2 NPs might be owing to its short diffusivity which inhibits the interface amongst the nanomaterials and microbial kinds (Chandran et al 2015). The heightened antibacterial efficacy detected for the 4% of Zr:SnO 2 NPs might be owed to the contact amid their amended shells and microbes owing to adsorption-desorption and also chemical/physical capabilities.…”
Section: Photocatalytic Mechanisms Of Obtained Photocatalystmentioning
confidence: 99%
“…All the Zr-doped SnO 2 NPs illustrate improved bacteriological retardant performance equated to the pristine sample besides the experienced pathogenic microbes. The inadequate antibacterial movement detected for the pristine SnO 2 NPs might be owing to its short diffusivity which inhibits the interface amongst the nanomaterials and microbial kinds (Chandran et al 2015). The heightened antibacterial efficacy detected for the 4% of Zr:SnO 2 NPs might be owed to the contact amid their amended shells and microbes owing to adsorption-desorption and also chemical/physical capabilities.…”
Section: Photocatalytic Mechanisms Of Obtained Photocatalystmentioning
confidence: 99%
“…At a concentration of 4 mg or above, Ce doped SnO 2 NPs showed potent antibacterial activities (Table 1). Previously, other metal ions doped with SnO 2 like Co-doped SnO 2 , Cu-doped SnO 2 , Fe-doped SnO 2 , and Ag-doped SnO 2 nanoparticles have also been reported for their antibacterial activities (Chandran et al, 2015;Nasir et al, 2017;Ali et al, 2018;Baig et al, 2020;Sathishkumar and Geethalakshmi, 2020). Generally, nanoparticles kill the bacteria through cell membrane disruption, free radical formation causing reactive oxygen species responsible for antibacterial action (Sirelkhatim et al, 2015).…”
Section: Analysis Of Antimicrobial Activitymentioning
confidence: 99%
“…Apart from antimicrobial activities, other important biological properties like anticancer, antitumor, and antioxidant activities have also been reported using green synthesized SnO 2 nanoparticles (Kamaraj et al, 2014;Khan et al, 2018). However, when doped with transition metal ions, SnO 2 disinfects microbes with good efficiency, i.e., Co-doped SnO 2 and Ag-doped SnO 2 nanoparticles have shown potent antibacterial activities (Chandran et al, 2015;Nasir et al, 2017;Qamar et al, 2017;Ali et al, 2018). Only a few reports are available on antimicrobial activities of Ce doped metal oxide NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Toloman et al, [22] have reported that the photocatalytic activity of SnO 2 was enhanced due to cobalt doping and they observed the fast trapping of photogenerated electrons by the Co dopants. Chandran et al, [23] synthesized SnO 2 with different concentration of Co 2+ they observed a highest photodegradation of Co/SnO 2 . Moreover, Mani et al, [24] prepared SnO 2 shows the band gap energy is reduced with the codoping and they observed a highest photodegradation.…”
Section: Introductionmentioning
confidence: 99%